Alleviation of carer strain during the use of the NeuroPage device by people with acquired brain injury. Issue 7 (25th February 2009) - Teasdale, Thomas W; Emslie, Hazel; Quirk, Kirsten; Evans, Jonathan; Fish, Jessica; Wilson, Barbara A
Abstract : Background: Previous studies have demonstrated the efficacy of a paging system, NeuroPage (Cambridgeshire Primary Care Trust Corporation, Fulbourn, Cambridgeshire, UK), in compensating for memory and planning dysfunctions in people with acquired brain injury (ABI; mainly stroke or traumatic brain injury). In this study, the degree to which this efficacy is accompanied by a reduced experience of strain among carers of patients with ABI was investigated. Methods: Carers of 99 people with ABI completed a questionnaire concerning strain resulting from caring for the injured individual. The questionnaire was completed at the following three time points: before the use of NeuroPage, at the end of a 7-week period of use, and, for one subgroup, a further 7 weeks after withdrawal of NeuroPage. Results: There were significant reductions in strain reported by carers following the 7-week period of NeuroPage use (Cohen's d = 0.3–0.4). This finding persisted when the carer was a spouse or a parent. The reduced strain among carers continued even after withdrawal of NeuroPage. Conclusion: The efficacy of the NeuroPage paging system for people with ABI appears to result in reduced strain for their carers.